PALYNOSTRATIGRAPHY AND PALAEOENVIRONMENTS OF DELTA -32H WELL NIGER DELTA, NIGERIA - Obiosio E.O.,; Nwaejije E.C., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2017)
Twenty-five ditch cutting samples from Delta – 32H well was analyzed for their lithologic and palynologic content.Four distinct lithofacies have been demarcated from the well that show alternations of the sandstone, siltstone and shale suggesting that the studied well penetrated the Agbada Formation of the Niger Delta. An Early Middle Miocene to Middle Miocene age was recorded for the well based on the recovery of a combination of spores and pollens including; Zonocostites ramonae, Retibrevitricolporites obodoensis, Psilatricolporites crasus, Retitricolporites irregularis and Pachydermites diederixi. The palynological zones; Monoporites annulatus taxon range zone Zonocoltites ramonae interval zonewas proposed for this study and they conform to the P680 and P720 subzones of Evamy et al. (1978). The presence of Magnastriatites howardi, Pachydermites diederixi,Zonocostites ramonaeand Monoporites annulatus as well as foram test linings suggests that the interval studied represents mainly deposition in a coastal to marginal marine setting, this marine influence and high percentage of Zonocostites ramonae suggests deposition in mangrove environments. Due to the dominance of mangrove pollens over the occurrence of the single savanna species (Monoporites annulatus), the sediment of the studied well was most likely deposited in mangrove environment under a wet climatic conditions during the Miocene.